Higher Risk of Preeclampsia Among Overweight and Obese Pregnant Women Compared to Normal BMI Women - Faradiyan Kencana; Ani Retno Prijanti; Yuditiya Puwosunu; Wimba Widagdo Dinutanayo; Adinda Juwita Sari (Jurnal Kesehatan, 2025)
Preeclampsia is a pregnancy complication characterized by hypertension and proteinuria, affecting 2–8% of pregnancies worldwide, with a prevalence of 24% in Indonesia. Its etiology remains unclear due to its complex, multifactorial nature, and several factors, such as age, obesity, pre-existing conditions, and multiple pregnancies, may influence its occurrence. This study aims to investigate the relationship between body mass index (BMI) and preeclampsia in pregnant women. An analytical observational study was conducted using purposive sampling, involving 18 participants in each group. Secondary data were obtained from medical records at Rumah Sakit Cipto Mangunkusumo, Rumah Sakit Budi Kemuliaan, and Puskesmas Senen. Statistical analysis was performed using the Chi-square test. Results show that 17 respondents (47.2%) with overweight or obesity had preeclampsia, whereas 8 respondents (22.2%) with normal BMI did not. The Chi-square test indicated a significant association between BMI and preeclampsia (p=0.007). Higher BMI is significantly associated with preeclampsia. Maintaining a healthy BMI during pregnancy may reduce the risk of this condition.